Inoculation of Bacillus velezensis Bv-116 and its bio-organic fertilizer serve as an environmental friendly biocontrol strategy against cucumber Fusarium wilt - Li, Haolong; Zhao, Shanshan; Zhang, Xueying; Yang, Fengyuan; Feng, Changsong; Huang, Yuhang; Tang, Xiaoxue; Sun, Pintian; Wang, Yanping (Frontiers in Plant Science, 2024)
The aim of this study was to evaluate the effects of Bacillus velezensis Bv-116 and its bio-organic fertilizer on the control of cucumber Fusarium wilt caused by Fusarium oxysporum f. sp. Cucumerinum (FOC), the promotion of growth of cucumber seedlings, and the soil microbial community. B. velezensis Bv-116 exhibited an inhibition rate of 84.93% against FOC, as well as broad-spectrum inhibitory activities against other soil-borne plant pathogenic fungi. Fermentation products of B. velezensis Bv-116 destroyed the cell structure of FOC and inhibited the growth of FOC mycelium. These products were identified as volatile antimicrobial gases, proteases and cellulases. In the greenhouse pot experiment, both B. velezensis Bv-116 and its bio-organic fertilizer exhibited significant promoting effects on cucumber growth, and a significant reduction in the incidence and disease severity index of cucumber wilt (p < 0.05). Analysis of the microbial community structure of cucumber rhizosphere soil revealed that inoculation of B. velezensis Bv-116 and its bio-organic fertilizer increased the abundance of genera with biocontrol capabilities against plant pathogens. In addition, inoculation of the bio-organic fertilizer reversed the excessive proliferation of Fusarium and Acidobacteria. Our results suggest the potential of inoculating B. velezensis Bv-116 and its bio-organic fertilizer as an environmentally friendly biocontrol strategy against cucumber wilt.